Encouraging ESL Discourse Exchanges via Facebook : A Study on Engineering Students - Kho, Marcus Gee-Whai; Chuah, Kee-Man (Technology and Innovation Conference 2015, 2015)
Online social networks have been widely used by educators as an alternative tool for language teaching and learning. In this study, Facebook is used as a tool to facilitate students ‟discussion activity. The activity involved 85 students who enrolled in a compulsory English course. The students were added and grouped in the “Facebook Group” named „AE101 Communicative English 1, December 2011 Session,” which was created by the researcher. After completing the activities in the Facebook group, the students were requested to complete a questionnaire comprising 4-point-Likert-scale questions and two structured questions. The results showed that the students felt that participating in group activities in the Facebook group made learning more interesting. Besides that, they felt comfortable expressing and sharing their ideas with their other coursemates, and they also learnt new vocabulary from reading the comments written by their coursemates. However, the collaboration between lecturer and students is essential in determining the success of implementing learning activities via Facebook.